UPAYA MENINGKATKAN PERKEMBANGAN MORAL ANAK USIA DINI MELALUI MENDONGENG DI TK DHARMAWANITA - Rakihmawati, Yusmiatinengsih (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2012)
The moral development of children at Dharmawanita kindergarten in Padang State University is still low, it seems that there are still children with less understanding of good and bad attitude from their behaviors, like disturbing children, less emphaty feeling and unhappy to play with their friends, and also unused to say thank. One of the causes are the teacher’s effort to grow morale and incorrect method in teaching it. The purpose of this research is to fix the teacher’s ways in growing morale lesson through educated and joyful fables. This research is the classroom action research, the research which increases the learning quality. The research data done by observation and interview. The classroom action research done in two cycluses. The result of this research had shown that there is the increase of children morale development, in cyclus 1, the moral development of children was still low, after cyclus II had been done, there was increasement. Based on the classroom action research, there was an increase of children morale development, it seemed before the action in the early percentage of children ability which was very high 13,23 %, in cyclus I it got increased into 36, 76 %, meanwhile in cyclus II, it got great increased into 77.44%. it shows that there is an increasement of children morale development from the early action before cyclus till cyclus II. The conclusion is telling fable can increase the children morale development. The writer suggests to the readers that this thesis can be used as the source to explore the knowledge increasing the children morale development.